The way west [compact disc, unabridged] : a novel - Guthrie, A. B., Jr. (Alfred Bertram), 1901-1991 (Dreamscape Media, 2013)
Second in the epic adventure Big Sky series. The wise and paternal mountain man Dick Summers agrees to pilot a wagon train full of 'greenhorns' on a journey from Missouri to Oregon. The passengers confront not only the wild grandeur of the untamed west, but also their own reasons for leavign everything behind. They struggle with the imperfect reality of their long held dreams. Resolve is tested, nature is conquered, and men are made or unmade in this timeless classic.